Flexoelectric measurements of a bent-core nematic liquid crystal. - Salter, P; Tschierske, C; Elston, S; Raynes, E (American Physical Society, 2011)
A large flexoelectric polarization might be expected for a bent-core nematic liquid crystal, due to the combination of molecular shape and transverse dipole component. In this study a bent-core nematic compound is doped to be highly chiral, and measurements of the difference in flexoelectric coefficients (e(1)-e(3)) are carried out by exploiting the chiral flexoelectro-optic effect. The measured flexoelectric coefficients are greater than those for many conventional calamitic nematics, but several orders of magnitude lower than recent reports on other bent-core compounds. The influence of the bent molecular shape on the nematic phase is evident from measurements of the elastic constants, where an unusually low ratio of k(3) to k(1) indicates that bend distortions of the director are relatively lower in energy compared to those involving splay.